Teologi Penggembalaan Yehezkiel Dalam Menghadapi Tantangan Kehidupan Jemaat - Linda Zenita Simanjuntak; Samuel Abdi Hu; Lukgimin Aziz (Manna Rafflesia, 2021)
This paper departs from ideas on facts in various parts of the world, especially the shepherding segment of Christian theology. As a prophecy, of course, the prophet Ezekiel had many essential messages for the life of the Shepherds at that time. Ezekiel 34 as one of the crucial parts of prophecy for today's readers, especially the field of practical theology deserves to be studied to obtain meaningful guidance for Pastors of the Congregation in shepherding a group of people who are facing various challenges in life. These various challenges were even more complicated when the corona pandemic was declared in 2020. By using the literature review method, the researcher explores various works of literature to answer the needs in the field, especially pastoral theology as part of practical theology. The results of the research state that the spirit of shepherding must not be diminished by the increasingly complex challenges of life. This prophetic content in Ezekiel 34 addresses two different areas, namely the judgment of hope in Christ. As a prophecy, Ezekiel 34 gives the sheep the joyous hope of waiting for God's intervention during misleading shepherding practices. On the other hand, some Shepherds actually have the opportunity to show strength and leadership. God has given wise tools and wisdom to the Pastors to lead the congregation to the comfort and comfort of life both physically and spiritually.